How the 1963 Equal Pay Act and 1964 Civil Rights Act Shaped the Gender Gap in Pay - Martha J. Bailey; Thomas Helgerman; Bryan Andrew Stuart (Institute of Labor Economics (IZA), 2023)
In the 1960s, two landmark statutes—the Equal Pay and Civil Rights Acts—targeted the long-standing practice of employment discrimination against U.S. women. For the next 15 years, the gender gap in median earnings among full-time, full-year workers changed little, leading many scholars to conclude the legislation was ineffectual. This paper revisits this conclusion using two research designs, which leverage (1) cross-state variation in pre-existing state equal pay laws and (2) variation in the 1960 gender gap across occupation-industry-state-group cells to capture differences in the legislation's incidence. Both designs suggest that federal anti-discrimination legislation led to striking gains in women's relative wages, which were concentrated among below-median wage earners. These wage gains offset pre-existing labor-market forces which worked to depress women's relative pay growth, resulting in the apparent stability of the gender gap at the median and mean in the 1960s and 1970s. The data show little evidence of short-term changes in women's employment but suggest that firms reduced their hiring and promotion of women in the medium to long term. The historical record points to the key role of the Equal Pay Act in driving these changes.
Keywords: J16; J71; N32; 330; gender gap; Equal Pay Act; Civil Rights Act